1978
DOI: 10.1073/pnas.75.10.5071
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric budding of viruses in epithelial monlayers: a model system for study of epithelial polarity.

Abstract: Infection of two different lines of polarized epithelial cells grown as monolayers with several types of enveloped viruses results, for each virus type, in a characteristic asymmetric budding of virions. Influenza virus (WSN strain), simian virus 5, and Sendai virus bud exclusively from the free (apical) surface of the cells, while vesicular stomatitis virus acquires its envelope only from the basolateral plasma membrane. Because different viruses select specific domains of plasma membrane in the same cell typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 452 publications
(53 citation statements)
references
References 13 publications
0
53
0
Order By: Relevance
“…the apical and the basolateral membranes. Indeed it has been demonstrated that these domains appear to have different protein [66] and lipid [67] compositions. From the similar morphological appearance [68,69] and the complementarity aspect [70] it has been proposed that the 'tight junctions' elements or strands reflect inter-bilayer tubes with the lipids in the H H orientation.…”
Section: Vb Lipidic Particles and Related Structuresmentioning
confidence: 99%
“…the apical and the basolateral membranes. Indeed it has been demonstrated that these domains appear to have different protein [66] and lipid [67] compositions. From the similar morphological appearance [68,69] and the complementarity aspect [70] it has been proposed that the 'tight junctions' elements or strands reflect inter-bilayer tubes with the lipids in the H H orientation.…”
Section: Vb Lipidic Particles and Related Structuresmentioning
confidence: 99%
“…At a late stage of virus infection, the vRNPs exit the nucleus to assemble and bud from the apical plasma membrane of polarized cells (3). The trafficking of the vRNPs into and out of the nucleus is a tightly regulated process (7).…”
mentioning
confidence: 99%
“…1). It has been shown previously that the SeV is released from epithelial cells in a polarized manner, predominantly at the apical surface [3]. The polarity properties of the adapted virus released from polarized MDCK cells were examined by infecting cells grown on inserts and collecting and determining the virus yields in both the apical and the basal media after predetermined intervals, in triplicate experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Each virus has been observed to have a specific preference for budding direction in polarized epithelial cells. Enveloped virus is usually released preferentially by budding at the apical plasma membrane and it has been previously demonstrated that the wild type SeV is released predominantly, though not exclusively from the apical surface of polarized epithelial cells [3], in contrast with the F1-R mutant SeV virus which is released from both the apical and basolateral surfaces [25,27]. The polarized entry and release of SeV play a role in the pathogenesis of the disease.…”
mentioning
confidence: 99%